2017
DOI: 10.1002/art.40034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional and Expression Polymorphisms Associated With Risk for Antineutrophil Cytoplasmic Autoantibody–Associated Vasculitis

Abstract: ObjectiveTo identify risk alleles relevant to the causal and biologic mechanisms of antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV).MethodsA genome‐wide association study and subsequent replication study were conducted in a total cohort of 1,986 cases of AAV (patients with granulomatosis with polyangiitis [Wegener's] [GPA] or microscopic polyangiitis [MPA]) and 4,723 healthy controls. Meta‐analysis of these data sets and functional annotation of identified risk loci were performed, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 143 publications
(172 citation statements)
references
References 42 publications
6
159
1
6
Order By: Relevance
“…This predicts that different HLA molecules would be involved in initiating the MPO-ANCA autoimmune response versus the PR3-ANCA autoimmune response. This was in fact observed in patients with ANCA vasculitis by genome-wide association studies that showed specific, and different, HLA associations with MPO-ANCA and PR3-ANCA vasculitis (16,17). Not surprisingly given their lineal role in immune responses, the HLA associations correlated better with ANCA specificity than with clinicopathologic phenotypes.…”
Section: Genesis Of Anca Autoimmunitymentioning
confidence: 84%
See 2 more Smart Citations
“…This predicts that different HLA molecules would be involved in initiating the MPO-ANCA autoimmune response versus the PR3-ANCA autoimmune response. This was in fact observed in patients with ANCA vasculitis by genome-wide association studies that showed specific, and different, HLA associations with MPO-ANCA and PR3-ANCA vasculitis (16,17). Not surprisingly given their lineal role in immune responses, the HLA associations correlated better with ANCA specificity than with clinicopathologic phenotypes.…”
Section: Genesis Of Anca Autoimmunitymentioning
confidence: 84%
“…Both antibodies (34) and T cells (35) specific for complementary PR3 have been detected in patients with ANCA vasculitis. Evaluation of the functional significance of ANCA vasculitis genome-wide association study data also suggested a role for immune recognition of complementary peptides by T cells (17).…”
Section: Genesis Of Anca Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome-wide association studies have identified several gene polymorphisms that are associated with susceptibility to GPA. These analyses have been limited to the study of selected SNPs however, and have not examined potentially important structural variants such as promoter microsatellites (48, 49). While patients with GPA had a greater prevalence of high expression MIF genotypes when compared to healthy controls, healthy controls also had a fair percentage of high expression MIF genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The PRTN3 colocalization illustrates how the genetic associations with cellular and molecular phenotypes can be combined to elucidate disease pathogenesis. rs138303849-C, a variant upstream of PRTN3 (encoding proteinase-3, PR3), is known to be associated with an increased risk of a vasculitis characterised by autoantibodies against PR3 (Merkel et al 2017) . This variant is an eQTL in whole blood (GTEx Consortium 2015) and we recently showed that the risk allele is associated with increased PR3 concentration in plasma .…”
Section: The Cellular Origins Of Plasma Proteinsmentioning
confidence: 99%